2021
DOI: 10.1002/bmc.5241
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis reveals potential biomarkers and serum metabolomic profiling in spontaneous intracerebral hemorrhage patients using UPLC/quadrupole time‐of‐flight MS

Abstract: Spontaneous intracerebral hemorrhage (ICH) accounts for 10-20% of all strokes and contributes to higher mortalities and severe disabilities. The aims of this study were, therefore, to characterize novel biomarkers, metabolic disruptions, and mechanisms involving ICH. A total 30 ICH patients and 30 controls were enrolled in the study, and their clinical characteristics were analyzed. Nontargeted metabolomic analysis was conducted using ultra-performance liquid chromatography quadrupole time-of-flight tandem mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our search resulted in one study related to metabolome profiling in ICH patients. Sun et al, 2021 performed non-targeted metabolomic analysis on serum samples obtained from ICH patients [ 19 ]. The study identified 11 metabolites of significance that are associated with multiple pathophysiological pathways following ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Our search resulted in one study related to metabolome profiling in ICH patients. Sun et al, 2021 performed non-targeted metabolomic analysis on serum samples obtained from ICH patients [ 19 ]. The study identified 11 metabolites of significance that are associated with multiple pathophysiological pathways following ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Still, in the clinical setting, imaging modalities used for diagnosis may not reveal any changes early on and may be time-consuming, demonstrating the need for novel and sensitive biomarkers for early diagnosis. Thus far, studies were able to identify metabolomic biomarkers of transient ischemic attack (TIA) ( 35 ), ischemic ( 26 , 36 ) and hemorrhagic stroke ( 37 , 38 ), metabolites capable of distinguishing between the stroke types ( 39 41 ) and stages ( 42 ), but also to differentiate between stroke and stroke mimics ( 43 ). It is evident that there is strong diagnostic potential from discovering differential biomarkers.…”
Section: Stroke Metabolomicsmentioning
confidence: 99%